Financial derivative and energy market valuation : theory and implementation in MATLAB - Mastro, Michael A., 1975- (Wiley, 2012)
A road map for implementing quantitative financial models Financial Derivative and Energy Market Valuation brings the application of financial models to a higher level by helping readers capture the true behavior of energy markets and related financial derivatives. The book provides readers with a range of statistical and quantitative techniques and demonstrates how to implement the presented concepts and methods in Matlab®. Featuring an unparalleled level of detail, this unique work provides the underlying theory and various advanced topics without requirin.